Food Anxiety in Globalising Vietnam - Ehlert, Judith (Springer Nature, 2019)
Based on empirical research, this book focuses on the ambivalences and contraditions of eating in Vietnam. Against the background of an emerging consumer society and the globalisation of the agro-food system, eating becomes centre stage for people's bodily integrity, social differentiation, identity projects as well as a lynchpin for national and international food policies.